Extrusion-based additive manufacturing of Mg-Zn/bioceramic composite scaffolds. (1st October 2022) - Dong, J.; Lin, P.; Putra, N.E.; Tümer, N.; Leeflang, M.A.; Huan, Z.; Fratila-Apachitei, L.E.; Chang, J.; Zadpoor, A.A.; Zhou, J.
Abstract : The treatment of femoral nonunion with large segmental bone defect is still challenging. Although magnesium alloys have been considered potential materials for such a treatment, their application is limited by their fast degradation. Adding bioceramic particles into magnesium to form Mg-matrix composites is a promising strategy to adjust their biodegradation rates and to improve their mechanical properties and cytocompatibility further. Here, we developed an extrusion-based additive manufacturing technique to fabricate biodegradable Mg-Zn/bioceramic composite scaffolds ex-situ . Inks carrying a Mg-Zn powder and 5, 10 and 15% β-tricalcium phosphate (TCP) powder particles were investigated regarding the dispersion of β-TCP particles in the inks and viscoelastic properties. Optimally formulated inks were then employed for subsequent 3D printing of porous composite scaffolds. The in vitro biodegradation rate of the scaffolds containing 5% β-TCP decreased to 0.5 mm/y, which falls within the range desired for critical-sized bone substitution. As compared to the monolithic Mg-Zn scaffolds, the elastic moduli and yield strengths of the composite scaffolds were much enhanced, which remained in the range of the cancellous bone properties even after 28 d of in vitro degradation. The Mg-Zn/5TCP and Mg-Zn/10TCP scaffolds also exhibited improved biocompatibility when cultured with preosteoblasts, as compared to Mg-Zn scaffolds. In addition, the ALP activity and mineralization level of the composite scaffolds were much enhanced in the extracts of the composite scaffolds. Taken together, this research marks a great breakthrough in fabricating porous Mg-matrix composite scaffolds that meet several design criteria in terms of appropriate biodegradation rate, mechanical properties, and bioactivity. Statement of significance: The treatment of posttraumatic femoral nonunion with large segmental bone defect is still challenging. In this study, we developed a multi-material extrusion-based additive technique to fabricate porous Mg/bioceramic composite scaffolds for such a treatment. The technique allowed for the fine-tuning of printable inks to optimize the dispersion of micro-sized particles. The relative densities of the struts of the fabricated composite scaffolds reached 99%. The added bioceramic particles (β-TCP) exhibited proper interfacial bonding with the Mg alloy matrix. The porous Mg-based composite possessed desired biodegradability, bone-mimicking mechanical properties throughout the  in vitro  biodegradation period and improved bioactivity to bone cells. These results demonstrated great prospects of extrusion-based 3D printed porous Mg materials to be developed further as ideal biodegradable bone-substituting materials. Graphical abstract: Image, graphical abstract